2013
DOI: 10.1002/pro.2250
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens epsilon toxin H149A mutant as a platform for receptor binding studies

Abstract: Clostridium perfringens epsilon toxin (Etx) is a pore-forming toxin responsible for a severe and rapidly fatal enterotoxemia of ruminants. The toxin is classified as a category B bioterrorism agent by the U.S. Government Centres for Disease Control and Prevention (CDC), making work with recombinant toxin difficult. To reduce the hazard posed by work with recombinant Etx, we have used a variant of Etx that contains a H149A mutation (Etx-H149A), previously reported to have reduced, but not abolished, toxicity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 39 publications
4
60
0
Order By: Relevance
“…Previous studies have shown that mutant ETX proteins with amino acid substitutions near F199 are defective in binding MDCK cells, but are not defective in binding human ACHN cells. 13 Binding assay of toxins on human ACHN cells was also performed, and we found rETX was more likely to bind to ACHN cells. In contrast, rETX F199E was defective in binding to ACHN cells (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Previous studies have shown that mutant ETX proteins with amino acid substitutions near F199 are defective in binding MDCK cells, but are not defective in binding human ACHN cells. 13 Binding assay of toxins on human ACHN cells was also performed, and we found rETX was more likely to bind to ACHN cells. In contrast, rETX F199E was defective in binding to ACHN cells (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…13 Our previous study also showed that C-terminal peptide reduced toxicity of ETX probably via covering receptorbinding region in domain III. 30 Therefore, there is still a possibility that the receptor binding region is located in domain III.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…L363A -For expression of eGFP-⌬6PLY L363A , recombinant plasmid was transferred into Escherichia coli Rosetta 2 (DE3) cells (Merck, Darmstadt, Germany), and expression of eGFP-⌬6PLY L363A was induced using the autoinduction system as described previously (51).…”
Section: Expression and Purification Of Egfp-⌬6plymentioning
confidence: 99%
“…However, ε-toxin has no equivalent to domain I of aerolysin, and the structural homology between the N-terminal ε-toxin domain and domain II in aerolysin is much less than that between the rest of ε-toxin and domains III and IV of aerolysin. A cluster of surface-exposed hydrophobic aromatic residues are present in this domain, which have been shown to be important for interactions with target cells [67]. Chassin et al [68] demonstrated that, unlike aerolysin, the ε-toxin receptor is not GPI-anchored, as PI-PLC treatment of target cells does not impair binding or complex formation.…”
Section: Aerolysin-like Toxins ε-Toxinmentioning
confidence: 99%